2021
DOI: 10.1213/ane.0000000000005640
|View full text |Cite
|
Sign up to set email alerts
|

The Facilitatory Effects of Adjuvant Pharmaceutics to Prolong the Duration of Local Anesthetic for Peripheral Nerve Block: A Systematic Review and Network Meta-analysis

Abstract: BACKGROUND: Peripheral nerve block (PNB) with perineural local anesthetic is used for anesthesia or analgesia with many benefits. To extend these benefits, various adjuvant drugs have been used to prolong the duration of analgesia. We aimed to evaluate the effectiveness of various adjuvants at prolonging the duration of sensory and motor blockade for PNB. METHODS: A network meta-analysis of placebo-controlled and active randomized controlled trials was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 31 publications
1
43
0
4
Order By: Relevance
“…is might be partly due to the effects of the dexamethasone added to ropivacaine. Previous studies have indeed shown that adding dexamethasone enhances the effects of peripheral nerve block and prolongs the duration of the sensory block of local anesthetics used for peripheral nerve blocks [16,17]. Possible beneficial mechanisms of dexamethasone include peripheral/central anti-inflammatory effects, inhibition of ectopic neural discharge, suppression of nociceptive C fibers, and suppression of the neuropeptide immune response to injury [18].…”
Section: Discussionmentioning
confidence: 99%
“…is might be partly due to the effects of the dexamethasone added to ropivacaine. Previous studies have indeed shown that adding dexamethasone enhances the effects of peripheral nerve block and prolongs the duration of the sensory block of local anesthetics used for peripheral nerve blocks [16,17]. Possible beneficial mechanisms of dexamethasone include peripheral/central anti-inflammatory effects, inhibition of ectopic neural discharge, suppression of nociceptive C fibers, and suppression of the neuropeptide immune response to injury [18].…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvants Dexamethasone, dexmedetomidine, clonidine and fentanyl have all been shown to prolong sensory and motor block duration, as well as increasing the time to first analgesia. 12 Among these adjuvants, dexamethasone seems to be the most effective. 12-13 a 2 -adrenergic agonists Clonidine prolongs sensory and motor block, and increases the time to first analgesia compared with placebo, but to a lesser degree than dexmedetomidine.…”
mentioning
confidence: 99%
“…12-13 a 2 -adrenergic agonists Clonidine prolongs sensory and motor block, and increases the time to first analgesia compared with placebo, but to a lesser degree than dexmedetomidine. 12,[14][15] Recent meta-analyses have shown that compared with placebo, dexmedetomidine prolonged a brachial plexus block by 292 minutes (95% CI: 245 to 329) and clonidine by 176 minutes (95% CI: 118 to 205). In the studies directly comparing the two a 2 -agonists, dexmedetomidine prolonged analgesia by approximately three hours.…”
mentioning
confidence: 99%
See 2 more Smart Citations